The politics and ethics of the just price : ethnographies of market exchange - Luetchford, Peter; Orlando, Giovanni (Emerald Publishing Limited, 2019)
Prices permeate contemporary life. From the cost of basic foodstuffs in developing countries to the pay of CEOs in rich ones, the question of the politics and ethics of pricing everything through the market dominates public life. At the same time, we know that dilemmas about how to value fairly, but also efficiently, goods and services have been with us for more than two thousand years, since the times of Aristotle in Ancient Greece. Through the course of the centuries, important thinkers like Thomas Aquinas, Adam Smith and Karl Marx all devoted considerable effort to try to understand how prices could reflect the intrinsic worth of the objects workers produce and exchange with other people. This is the question of the "just price." This volume represents the first systematic attempt to address this ancient debate through the use of qualitative empirical research, particularly ethnography. The volume comprises a substantial introduction that sets out the terms of the debate, proposing four different approaches to the just price, plus eight case studies based on fieldwork carried out in four different continents (Africa, Asia, Europe and Latin America), ranging from topics such as fair trade, human rights and recycling, to organic agriculture, the rose oil industry, rural and urban marketplaces. Bringing together the most recent scholarship in economic anthropology and associated fields to investigate the social, political and ethical consequences of market prices on ordinary people, this book is of interest to researchers in anthropology, sociology, history and geography.
Prelims -- Introduction toward an anthropology of the just price: history, ethnography, and critique -- Market, morality and (just) price: the case of the recycling economy in Turkey -- When the big ones abandon the marketplace: morals and politics of price in equatorial guinea -- Pecunia non olet but does rose money smell? On rose oil prices and moral economy in Isparta, Turkey -- What's in a just price? Challenging values at an organic cooperative in southern Spain -- Market relations as social relations: prices and the moral economy of corn and bean trading in rural Nicaragua -- Tuscan values -- Just compensation? The price of death and injury after the Rana Plaza Garment Factory collapse -- Practicing the just price: fair trade and the limits of ethical consumption in the global north -- Afterword -- Index.
Includes index.
Print version record.
Keywords: Prices -- Case studies; Markets -- Case studies; Social Science -- Anthropology -- General; Sociology & anthropology